Стратегії розвитку соціально-освітніх програм для тимчасових робітників у діяльності освітніх організацій Латинської Америки - Жижко, Олена (Studies in Comparative Education, 2015)
У статті розглянуто стратегії розвитку соціально-освітніх програм для тимчасових робітників у діяльності освітніх організацій Латинської Америки. Встановлено, що пріоритетом розвитку латиноамериканської освіти, зокрема соціально-освітніх програм для тимчасових робітників, є поліпшення їх якості, упровадження сучасних навчальних технологій, орієнтація на позитивний міжнародний досвід. В статье рассмотрены стратегии развития социально-образовательных программ для временных рабочих в деятельности образовательных организаций Латинской Америки. Выявлено, что приоритетом развития латиноамериканского образования, в частности, социально-образовательных программ для временных рабочих, является улучшение их качества, внедрение современных учебных технологий, ориентация на положительный международный опыт. The strategies of development of socio-educational programs for temporary workers in educational institutions of Latin America were analyzed. The research shows that the main priority of Latin education development is quality improvement, introduction of new educational technologies, orientation to positive international expierence. It was established that the development of strategies of adult education in general and of socio-educational programs for temporary workers in particular had been developing in the Latin American region since the 50-ies of XX century. It resulted in formation of CREFAL, CEAAL, FIDEA and the organization of international and regional measures on adult education which laid the basis for the development of Latin American concept of adult education in the 60-80-ies of XX century. In the 80-90-ies of XX century the strategy for adult education gained progress with the implementation of special projects, such as PROMEDLAC, REDALF, «Regional Framework of Action for Education for All» and the launch of OEA, OEI, SITEAL, EPJA, ILCE, LLECCE and consolidated in the first decade of the XXI century along with the adoption of programs PRELAC, «Goals 2021», «European Union - Latin America» «EUROsociAL Educación» and others. It was established that from January 2011 in Latin America under the auspices of Spain launched a large-scale project in the field of education, aimed at further movement in the region towards social progress. This strategic direction is expressed in terms of social cohesion and overcoming inequalities in access to education. The proposed program of action involves a change in priorities toward improving the quality of Latin American education. On the basis of the sources in the original language we can distinguish the following strategic directions of development of adult education, including socio-educational programs for temporary workers in the Latin American region: - connection of educational activities with health projects or other programs of a social nature; - cooperation of government agencies with national and international private institutions, business communities, ONG; - Iintroduction of modern educational technologies; - focus on positive international experience.